Instrumen Hukum Administrasi terhadap Pengelolaan Berdimensi Kearifan Lokal pada Kawasan Kaldera Toba - Azan Pranoto (Journal of Legal and Cultural Analytics, 2022)
The purpose of this study is to determine the management of local wisdom in the Toba Caldera area in a review of administrative law. The method used in this research is descriptive, explanatory and juridical normative. This research was conducted in the Toba Caldera area, North Sumatra. In maintaining and preserving cultural values, customs and local wisdom, including the village of Turpuk in the formation of inter-regional cooperation based on Regional Regulations which were enhanced through Law no. 23 of 2014 in article 369 which states that cooperation is needed for efficiency and effectiveness of government administration. Then the arrangement of the Lake Toba area is very necessary to change the attitude shift from Anthropocentric to Ecocracy.